2020
DOI: 10.1093/aob/mcaa159
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal colonization outcompetes root hairs in maize under low phosphorus availability

Abstract: Background and Aims An increase in the root hair length and density, as well as the development of arbuscular mycorrhiza symbiosis, are two alternative strategies of most plants to increase the root-soil surface area under phosphorus (P) deficiency. Across many plant species, root hair length and mycorrhization density are inversely correlated. Root architectures, rooting density and physiology also differ between species. This study aims to understand the relationship among root hairs, arbus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 81 publications
6
28
0
1
Order By: Relevance
“…We expected that the rth3 plants would show higher colonisation levels, especially as mycorrhiza formation can actually compensate for the loss of root hairs in the rth3 mutant. By implementing an AMF inoculation experiment, Ma et al (2021) showed that the positive effects of mycorrhiza formation on plant growth and P acquisition in rth3 were 1.5-to 3.9-fold greater than in the wild-type, and AMF colonisation complemented growth and P acquisition defects of the mutant. Interestingly, mycorrhizas also effectively substituted root hairs in P uptake in barley (Jakobsen et al 2005).…”
Section: Arbuscular Mycorrhiza (Am) Formationmentioning
confidence: 99%
“…We expected that the rth3 plants would show higher colonisation levels, especially as mycorrhiza formation can actually compensate for the loss of root hairs in the rth3 mutant. By implementing an AMF inoculation experiment, Ma et al (2021) showed that the positive effects of mycorrhiza formation on plant growth and P acquisition in rth3 were 1.5-to 3.9-fold greater than in the wild-type, and AMF colonisation complemented growth and P acquisition defects of the mutant. Interestingly, mycorrhizas also effectively substituted root hairs in P uptake in barley (Jakobsen et al 2005).…”
Section: Arbuscular Mycorrhiza (Am) Formationmentioning
confidence: 99%
“…The majority of plant species, including crop species, are responsive to mycorrhizal symbiosis. In maize, arbuscular mycorrhiza formation has been demonstrated to be more important than root hairs for seedling growth under low P availability ( Ma et al, 2021). The degree to which plants respond to mycorrhizal symbiosis depends on: (1) the plant species and its root traits; (2) soil conditions, such as inherent fertility, pH, and management; and (3) AMF species.…”
Section: Introductionmentioning
confidence: 99%
“…AMF helps host-plants partly maintain their rate of development, despite the effects of stress, by regulating a series of signaling pathways between the plant and the fungus, thereby facilitating the photosynthetic rate and other gas exchange-related features (Huang et al, 2020). Inside plant roots and in the soil, AMF can substantially increase the surface area available for nutrient absorption by plants (Gavito et al, 2019;Ma et al, 2021). Therefore, in the case of mycorrhiza and Si, root traits in many cases are frequently bound to improve.…”
Section: Discussionmentioning
confidence: 99%